2014
DOI: 10.1080/1357650x.2014.891606
|View full text |Cite
|
Sign up to set email alerts
|

When right differs from left: Human limb directional asymmetry emerges during very early development

Abstract: The often observed directional asymmetry (DA) in human limb bones may have a genetic/developmental basis and/or could emerge from different mechanical loadings across sides due to handedness. Because behavioural lateralization in itself has a genetic basis, it has been suggested that DA in limbs could develop prenatally as a pre-adaptation to adult life. However, the presence of consistent differences in the size of left and right limb bones in early development is understudied. We study asymmetry in limb bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The Limb Symmetry Index (SI) values of the G_BS highlight large asymmetries (SI > 0.15) in five anthropometric parameters: hand length, palm length, hand span, ring finger and thumb; in the case of the G_NBS, large asymmetries were identified in eight anthropometric parameters: upper limb length, hand length, palm length, pinky finger, ring finger, middle finger, index finger and thumb. A series of studies carried out on athletes have identified asymmetry between the dominant and the non-dominant segment, which confirms the results of our study [46,78]. A study conducted on 36 handball players (average age 26.1 years) observed that the muscle mass and grip strength of the right upper limb is greater than that of the left; handball influences the asymmetric growth of body muscle hypertrophy [41].…”
Section: Discussionsupporting
confidence: 89%
“…The Limb Symmetry Index (SI) values of the G_BS highlight large asymmetries (SI > 0.15) in five anthropometric parameters: hand length, palm length, hand span, ring finger and thumb; in the case of the G_NBS, large asymmetries were identified in eight anthropometric parameters: upper limb length, hand length, palm length, pinky finger, ring finger, middle finger, index finger and thumb. A series of studies carried out on athletes have identified asymmetry between the dominant and the non-dominant segment, which confirms the results of our study [46,78]. A study conducted on 36 handball players (average age 26.1 years) observed that the muscle mass and grip strength of the right upper limb is greater than that of the left; handball influences the asymmetric growth of body muscle hypertrophy [41].…”
Section: Discussionsupporting
confidence: 89%
“…Intrinsic differences in anatomically bilaterally symmetric structures have long been suspected: acetazolamide teratogenizes only the right limb in rats ( Layton and Hallesy, 1965 ; Wilson et al, 1968 ) and nitroheterocyclics such as valproate also induce unilateral defects ( Coakley and Brown, 1986 ; Fantel et al, 1986 ). Directional asymmetry in limb size in human fetuses was recently reported ( Van Dongen et al, 2014 ). Left/right identity differences in bilaterally symmetric structures such as the limbs may be upstream of secondary patterning events such as dorsal/ventral axis appropriate to body side.…”
Section: Discussionmentioning
confidence: 90%
“…This DA could reflect a real biological phenomenon, or it could originate from the handedness of the measurer (Helm and Albrecht 2000). Differences in DA among traits have also been observed in humans and may have functional importance (related to behavioral lateralization; Auerbach and Ruff 2006), but also be of developmental origin (Van Dongen et al 2014). Absolute values of the random individual effects were used as estimates of AFA, thus after correcting for measurement error and directional asymmetry.…”
Section: Estimating Size and Afamentioning
confidence: 99%